678 Gastrointestinal Transit Patterns in Childhood Chronic Constipation. (October 2012) - Yik, YI; Cook, DJ; Veysey, DM; Tudball, CF; King, BS; Morris, KA; Cain, TM; Southwell, BR; Hutson, JM
Abstract : Background and Aims: Constipation may be a part of a generalized gastrointestinal (GI) tract disorder. Nuclear transit scintigraphy (NTS) provides transit through the stomach, small bowel, colon and anorectum. This study aimed to determine different colonic and rectal transit patterns in children with chronic constipation (CC) and their association with upper GI tract disorders. Methods: A retrospective analysis of NTS (1999–2011) performed in children with intractable CC. The 48-hour NTS protocol involved Gallium-67 citrate milk drink with images acquired at 0–2 hrs (gastric emptying study) and at 6, 24, 30 and 48 hrs (small bowel & colonic transit studies). The geometric centre calculation was based on % of radioactivity in each region of interest (ROI). Six ROIs were employed (1=pre-colonic, 2=ascending colon, 3=transverse colon, 4=descending colon, 5=recto-sigmoid colon and 6=toilet). Results: A total of 955 NTS was performed (1999–2011; 288 repeat & 667 new studies). In the 603 children (284 female, 2–23yrs, mean 8.5±4.1yrs) included for this study, 19% had normal colonic transit (NT), 52% slow colonic transit (ST) and 29% rapid proximal colonic transit (RT, Table 1 ). Only 1/3 of children had AR. About 20% of children had delayed gastric emptying & delayed small bowel transit. Conclusions: There are 3 distinct colonic transit patterns in children with CC: normal, slow & rapid. About 1/3 of children with CC had AR at 48 hrs & was associated with NT, ST and RT. In addition, 21–24% children with CC had upper GI tract transit disorders.